STUDI STABILITAS DINDING PENAHAN TANAH BERDASARKAN PENGARUH TINGGI DINDING RENCANA RETAINING WALL DESA MARGOMULYO KECAMATAN LOA JANAN - by, bob (KURVA S JURNAL MAHASISWA, 2014)
Margomulyo village is one of the villages located in District Loa JananRegency, the village is located in the mining area which led to several roadsleading to the village is experiencing landslides due to soil instability. On somestreets Village Margomulyo Loa Janan subdistrict are point landslide whichthen inhibits the flow of traffic and transportation.To overcome this avalanche handling efforts by using retaining wallconstruction. The purpose of the handling of avalanche course in order to avoidthe termination of the road so that it can interfere with the performance of theroad at that location. Retaining wall is a construction model of prevention oflandslides that have long been used ever since the ancient Roman era. With thedevelopment of construction technology fairly rapid construction of retainingwall has evolved into a variety of shapes and materials used, but theparameters of the construction is the ability to accept vertical and horizontalloads.The study on high retaining wall is one way to measure the level ofsuccess in the use of this type of construction for the prevention of avalanchesespecially on roads Margomulyo Village, District Loa Janan, Kutai regency.The limit problem in this study is more focussed includes, calculating thedimensions of a retaining wall using type counterfort, burdens the work is itsown weight, additional dead load, traffic load, the load pressure of the soil andearthquake loads, calculations using two alternative high dimensional plan thatis 3 meters and 5 meters with a segment length is 15 meters and the quality ofconcrete used is K.275, or 275 kg / cm2. From the calculation results can be thelargest vertical force 1848.8919 KN, and 685,802 KN greatest shear forces. Inthe 3 meter high wall construction secured against rolling, but the 5 meter highwall construction is not safe, especially on the y axis retaining wall. Whileunder the influence of shear retaining wall construction is quite safe.